Micromycete diversity and pathogenic potential in soils of long-term cultivated apple orchards - Demyanyuk, O.; Oliferchuk, V.; Yakovenko, R.; Synenko, D.; Pinheiro, M. N. Coelho; Symochko, L. (Frontiers in Microbiology, 2025)
IntroductionLong-term agricultural management can substantially alter soil microbial communities. The vertical distribution and ecological roles of micromycetes in deep soil profiles of perennial orchard systems remain poorly understood. This study examines the abundance, taxonomic composition, and stratification of micromycetes in dark gray soils of apple orchards cultivated continuously for over 90 years, with the aim of identifying microbiological hotspots and assessing their potential ecological functions.MethodsSoil samples were collected from 0-100 cm depths and analyzed using standard microbiological methods. Quantitative assessments of fungal abundance were based on colony-forming unit (CFU) counts, while qualitative analysis included isolation and identification of micromycetes to the species level. Structural indices were calculated to characterize species diversity, community stability, and vertical differentiation across soil layers.ResultsMicromycete abundance remained consistently high throughout the soil profile, ranging from 113 to 138 × 103 CFU g−1, indicating persistent fungal activity across depths. A total of 68 species belonging to 22 genera and three phyla (Mucoromycota, Mortierellomycota, and Ascomycota) were identified. Ascomycota dominated the mycobiome, accounting for 85% of species diversity. Aspergillus (14 species) and Penicillium (13 species) were present at all depths, suggesting their central role in shaping microbial hotspots. Rare taxa, such as Mucor hiemalis, Cladosporium cladosporioides, and Humicola spp., occurred at low frequencies (0.3–3.4%), contributing to community heterogeneity. Importantly, Fusarium culmorum, typically associated with chernozem soils, was detected for the first time in dark gray soils at 20–60 cm depths. Structural indices revealed clear stratification between surface and subsurface horizons, with greater species richness and community stability observed in the 0-60 cm layers.DiscussionThese findings demonstrate that long-term orchard cultivation supports vertically structured micromycete communities, with specific soil layers acting as microbiological hotspots essential for maintaining soil ecosystem functions. The substantial proportion of phytopathogenic taxa (28%) underscores potential risks to orchard health, while the novel detection of F. culmorum suggests shifts in fungal distribution driven by prolonged land use.